Penerpan Metode Muroja’ah dalam Meningkatkan Hafalan Al-Qur’an - Maruapey, Kamal; Khasanah, Uswatun; Sulistyowati (Jurnal Pendidikan Nusantara, 2022)
The original purpose of this research was to find out, 1) how to apply the muroja'ah method at Muhammadiyah Palur Elementary School, 2) what are the obstacles and solutions to the implementation of the muroja'ah method at Muhammadiyah Palur Elementary School. This type of research is qualitative using a narrative approach, as long as the data is obtained by the people involved in it, the paper, and the data obtained in the field. Data collection techniques resulted from interviews, observation and documentation. Data analysis techniques use data reduction, data presentation, and conclusions. The data validation technique uses technical triangulation, original triangulation, and time triangulation. what will happen from this research is that the application of the muroja'ah method to Muhammadiyah Palur Elementary School is, 1) muroja'ah together and listened to by assatidz, 2) muroja'ah memorizing with friends, 3) tahfidz exam for those who have completed minimum memorization of juz 30. The obstacles in applying the muroja'ah method are, 1) students are not focused, 2) students are lazy, 3) the environment is less effective. The solution to overcoming obstacles to the application of muroja'ah is, 1) the teacher must be creative in teaching, 2) the teacher must understand the characteristics of each student, 3) each student has a memorization control book and also muroja'ah. The results of the application of the muroja'ah method in Muhammadiyah Elementary Schools in memorizing the Qur'an are that students have confidence in increasing their memorization of the Qur'an and also class 2 B students are able to complete memorizing the Al-Qur'an in juz 30 and take the tahfidz exam in one sitting.